Islamic Religious Extension Methods In Counseling Residents In Medan City Social Protection Houses - Najwa Ulfi Rahmi; Nashrillah M. G (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the methods employed by Islamic religious Counselors in guiding inmates of the Medan City Social Protection House and to explore how these methods shape changes in religious understanding, behavior, worship discipline, and life motivation among the residents. The study adopts a descriptive qualitative design with data collection techniques including observation, semi-structured interviews, and documentation. The research informants consist of Islamic religious Counselors, employees of the Medan City Social Protection House, and selected inmates recruited through purposive sampling in accordance with the research focus. Data analysis was carried out through iterative processes of data reduction, thematic data presentation, and interpretive verification, while data validity was examined using source triangulation across different participant groups and data collection techniques. The findings indicate that Islamic religious Counselors predominantly employ interactive lectures, questions and answers, individual guidance, exemplary conduct, and habituation with materials on faith, worship, morals, and exemplary stories. These methods are in line with the Islamic da'wah approaches articulated in the Qur'an, namely bil hikmah, mau'izhah hasanah, and mujadalah billati hiya ahsan, and are operationalized in a humanistic and persuasive counseling context within the institution. The guidance activities contribute to strengthening residents’ religious understanding and fostering tendencies toward more disciplined worship and more constructive social behavior; however, these changes are gradual, vary across individuals, and remain contingent upon the residents’ own readiness and awareness to transform, as emphasized in the Qur’an. This study offers a contextualized conceptual account of Islamic religious counseling in social protection institutions by synthesizing da'wah methods, counseling practices, and social rehabilitation objectives, thereby providing an analytical framework that can inform future multisite or comparative studies on Islamic religious counseling for vulnerable social groups